TEACHER PERFORMANCE BASED ON SELF-EFFICACY AND LOCUS OF CONTROL - Edy Dharma; Hendrick Sasimtan Putra; Sherly Sherly (JURNAL MANAJEMEN MAKER STIE SULTAN AGUNG, 2024)
The purpose of this study is to determine the performance of Sultan Agung Private Junior High School teachers, assessed based on self-efficacy and locus of control. This study employs a quantitative research approach with the research subjects being 36 permanent teachers at Sultan Agung Private Junior High School. Data collection involves the use of questionnaires, interview interactions, and documentation. Validity and reliability testing are part of the research instrument validation. Data is analyzed using quantitative descriptive analysis techniques, including normality testing, regression analysis, correlation and determination testing, as well as hypothesis testing. The findings of this research can be summarized as follows: (1) The correlation between self-efficacy, locus of control, and teacher performance is both positive and significant, whether considered simultaneously and partially; (2) There exists a moderately high correlation between self-efficacy and locus of control with regards to teacher performance.